#TITLE_ALTERNATIVE# - RAMLAN (NIM12305039) pembimbing :Dr. Ir. Agus Laesanpura, M.S.,, SOFYAN
CRS stacking method is developed to enhance quality of seismic data. CRS stacking obtained by this method regularized and have better signal-to-noise ratio compared to original CMP gathers. zero-offset (ZO) CRS Stacking operator is a function from three CRS attribute which each other influence. CRS attributes give us more detail information about the subsurface consist of emergence angle α and the two radius of wavefront curvatures RNIP and RN. Those CRS attributes extracted from prestack seismic data using optimization scheme with coherence as objective function to obtain the best stacking surface in every zero-offset (ZO) sample. Aperture is most important parameters of zero-offset (ZO) CRS-stack. In this thesis, seismic data processed with zero-offset (ZO) CRS-Stacking method for synthetic. We verified the CRS Stack method on synthetic data the acquisition parameter used 3 km streamer length, 120 live channel and 141 source number. Recording time 4s and sampling interval 4ms. From the zero- offset (ZO) CRS-Stacking processing result there is seen a complex geology thrust fault (reverse fault) structure.